2019
DOI: 10.1186/s12886-019-1031-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in choroidal thickness and optic nerve head morphology after filtering surgery: nonpenetrating deep sclerectomy versus trabeculectomy

Abstract: BackgroundThe purpose of this study was to evaluate the changes in choroidal thickness and lamina cribrosa position after nonpenetrating deep sclerectomy (NPDS) and trabeculectomy.MethodsTwenty-three eyes with glaucoma that required filtering surgery were included (12 NDPS and 11 trabeculectomies) in this prospective observational study. OCT-enhanced depth imaging (OCT-EDI) was used to measure choroidal thickness, prelaminar tissue thickness and lamina cribrosa position before and 7 days and 1 month after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…In accordance with previous studies performed on trabeculectomy, we found a significant increase in CT both in macula and in peripapillary region after the decline of the IOP, already 24 h after surgery [ 3 , 7 10 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with previous studies performed on trabeculectomy, we found a significant increase in CT both in macula and in peripapillary region after the decline of the IOP, already 24 h after surgery [ 3 , 7 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the magnitude of morphological changes in the choroid and laminar region did not appear to be correlated with the IOP reduction magnitude or the baseline IOP value. Conversely, Buillot et al found a correlation between IOP variation linked to the MicroShunt and changes in macular choroidal thickness one week after surgery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, SFCT tends to be negatively correlated to IOP [ 33 , 34 , 35 , 36 , 37 , 38 ]. As both IOP and SFCT decrease in our study, IOP variation does not explain the SFCT decreases.…”
Section: Discussionmentioning
confidence: 99%